Prevalence and associated risk factors of bruise in the bovine carcass slaughtered Jimma Municipal Abattoir, Ethiopia - Mohammed, Ahmednur Ali; Wolde, Radeit; Mahamed, Samatar Abshir (PT. Mega Science Indonesia, 2025)
Bruising bovine carcasses is a significant concern in the meat industry and affects both animal welfare and economic outcomes. This study aimed to determine the prevalence of and associated risk factors for bruises in bovine carcasses in the Jimma Municipal Abattoir, Ethiopia. A cross-sectional study was conducted from October 2022 to May 2023; 384 randomly selected cattle were examined during ante- and postmortem inspections. Data on potential risk factors, including age, sex, breed, body condition, and causes of bruising, were collected. Visual inspection, palpation, and incision techniques were employed during the postmortem examination to identify and record the prevalence, anatomical location, and severity of bruises. Statistical analysis was performed via SPSS version 16.00, with nominal regression used to determine bruise rates and chi-square tests used to assess the associations between risk factors and bruise occurrence. A 95% confidence interval was applied, and differences were considered statistically significant at p<0.05. The study revealed a 24.48% prevalence of bruising, with stick beating (8.9%) being the most common cause. The anatomical distribution of the bruises varied, with the highest condemnation rates observed in the back and loin (6.25%). Statistical analysis revealed significant differences in bruise incidence based on age, sex, and body condition (p<0.05). A high prevalence of bruising has a substantial economic impact on the local meat industry. Factors such as improper handling during transportation significantly contribute to this issue. Recommendations include implementing awareness programs for stakeholders and enhancing animal welfare measures to mitigate economic losses and improve carcass quality.